Real exchange rate misalignment and business cycle fluctuations in Asia and the Pacific - Dessie Tarko Ambaw; Madhavi Pundit; Arief Ramayandi; Nicholas Sim (Asian Development Bank (ADB), 2022)
Real exchange rate (RER) misalignment, which is the deviation between the actual real exchange rate from its equilibrium, occurs frequently among developing economies. Studies have shown that RER misalignment may have negative economic implications, such as a reduction in economic growth, exports and export diversification, and an increased risk of currency crises and political instability. Using quarterly data for 22 sample economies from 1990 to 2018, this paper investigates the impact of RER misalignment on business cycles in Asia and the Pacific by employing a panel vector autoregression involving consumer price index (CPI) inflation, output gap, short-term interest rate, and RER misalignment. We find that RER overvaluation may lead to a reduction in CPI inflation and short-term interest rate. We also find that Asia and the Pacific is highly heterogeneous wherein the output gaps of some economies, particularly those in Southeast Asia, are more susceptible to RER misalignment shocks.
Keywords: D74; E32; F31; F41; O11; 330; real exchange rate misalignment; business cycle fluctuations